2016
DOI: 10.2485/jhtb.25.69
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Image Findings of the Nasopalatine Duct Region Using Multidetector-Row CT

Abstract: Distinguishing normal parts of the nasopalatine duct from nonodontogenic nasopalatine duct cysts can be difficult. This study aimed to establish the characteristic imaging findings of the nasopalatine duct region on multidetector-row computed tomographic (MDCT) images. The subjects were 122 patients (61 males, 61 females; mean age, 49.8 years; age range, 17-88 years) who underwent 64-MDCT imaging of the maxilla after providing informed consent. Anatomic variants of the nasopalatine duct were classified using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Kotaro et al [15] in their study found out that the average mesiodistal diameter of the incisive fossa was 3.3 mm and 2.8 mm in males and females respectively. Matsumura et al [16] in their study measured it as 3.1 mm and 3.3 mm in males and females respectively.…”
Section: Discussionmentioning
confidence: 93%
“…Kotaro et al [15] in their study found out that the average mesiodistal diameter of the incisive fossa was 3.3 mm and 2.8 mm in males and females respectively. Matsumura et al [16] in their study measured it as 3.1 mm and 3.3 mm in males and females respectively.…”
Section: Discussionmentioning
confidence: 93%
“…In our study, the MP width was found to be 2.25 mm in accordance with the literature. Ito et al [ 23 ], Al-Amery et al [ 21 ], Friedrich et al [ 20 ], and Tözüm et al [ 22 ] reported that this value was higher in men. Kajan et al [ 24 ] and Thakur et al [ 25 ] reported that the width of the canal was not statistically significant according to gender.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the measurements of the NPC in the sagittal section were frequently performed in the studies, but there were a limited number of studies in which the measurements were performed in the coronal section. Panjnoush et al [ 10 ] and Ito et al [ 23 ] reported that there was no statistically significant difference between IF and SF widths and gender, age, or dental status. In our study, there was a statistically significant difference between IF, SF widths, and age and gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A CT image is an indispensable for a differential diagnosis specially multidetector-row CT (MDCT) 18) . The observations of the present study are different from the previous studies reported in the literature.…”
Section: Discussionmentioning
confidence: 99%